Exploring the Interactions and Functional Implications of Dbp2 and the RSC Complex in Schizosaccharomyces pombe - Böhme, Jacqueline; Justus Liebig University Giessen (My University, 2025)
Transcription is a fundamental process by which genetic information encoded in DNA is transcribed into RNA, representing a crucial step in gene expression. This process is regulated by a variety of factors that influence both the activity and accessibility of DNA. One of the central mechanisms that control transcription is the remodeling of chromatin by dedicated complexes, which modulate transcriptional activity through alterations in chromatin structure, either in an activating or repressive manner. The RSC complex is involved in various cellular processes, particularly transcriptional regulation. Dbp2, an RNA helicase with diverse biological functions, is critical in mRNA processing and other RNA-related processes. In light of their potential interaction, this study investigates the functional connection between Dbp2 and the RSC complex in Schizosaccharomyces pombe. To this end, a modified auxin-inducible depletion system was successfully established, enabling inducible and rapid depletion of the RSC complex's essential subunit Snf21. Our results suggest an interaction between Dbp2 and the RSC complex in the nucleoplasm. Interestingly, however, the two components act independently concerning their cellular localization and function. Notably, the loss of Dbp2 results in impaired mRNA export, while the loss of the RSC complex does not directly affect this process. Furthermore, the influence of the RSC complex on gene expression was characterized in greater detail to thoroughly investigate its functional roles in transcriptional regulation and identify potential target genes. Through PolⅡ-ChIP-Seq experiments, we identified a surprising repressive effect of the RSC complex on various target genes, particularly those located near the telomeres. These findings provide new insights into the function of chromatin remodeling complexes and their role in transcriptional regulation. Our results contribute to the broader understanding of chromatin-based genome regulation and open new avenues for exploring the functional diversity of these complexes.
Keywords: ddc:540; ddc:570